Bictegravir/emtricitabine/tenofovir alafenamide combination in the management of kidney transplant patients with HIV receiving immunosuppressants. (3rd April 2022) - Lagoutte-Renosi, Jennifer; Flammang, Mylène; Ducloux, Didier; Bamoulid, Jamal; Royer, Pierre-Yves; Lepiller, Quentin; Clairet, Anne-Laure; Davani, Siamak; Muret, Patrice
Abstract: We report here a drug-drug interaction with tacrolimus in a HIV-positive patient with renal transplant, after switch from highly active antiretroviral therapy with boosted protease inhibitors to the combination bictegravir/emtricitabine/tenofovir alafenamide. Although the tacrolimus doses were adapted to take account of the pharmacokinetic interactions with protease inhibitors, a tacrolimus overdosage occurred in the patient nonetheless. Through this case report, we highlight the need to consider a sufficient timeframe of withdrawal of protease inhibitors, which induce a prolonged drug-drug interaction with tacrolimus. To conclude, we purport that the combination bictegravir/emtricitabine/tenofovir alafenamide could be an attractive alternative in the context of transplantation provided a discontinuation of boosted protease inhibitors for more than 48 hours before introducing tacrolimus.